Spinal neuromodulation mitigates myocardial ischemia-induced sympathoexcitation by suppressing the intermediolateral nucleus hyperactivity and spinal neural synchrony - Salavatian, Siamak; Kuwabara, Yuki; Wong, Benjamin; Fritz, Jonathan R.; Howard-Quijano, Kimberly; Foreman, Robert D.; Armour, J. Andrew; Ardell, Jeffrey L.; Mahajan, Aman (Frontiers in Neuroscience, 2023)
Myocardial ischemia disrupts the cardio-spinal neural network that controls the cardiac sympathetic preganglionic neurons, leading to sympathoexcitation and ventricular tachyarrhythmias (VTs). Spinal cord stimulation (SCS) is capable of suppressing the sympathoexcitation caused by myocardial ischemia. However, how SCS modulates the spinal neural network is not known. In this pre-clinical study, we investigated the impact of SCS on the spinal neural network in mitigating myocardial ischemia-induced sympathoexcitation and arrhythmogenicity. Ten Yorkshire pigs with left circumflex coronary artery occlusion-induced chronic myocardial infarction (MI) were anesthetized and underwent laminectomy and a sternotomy at 4 to 5 weeks post-MI. The activation recovery interval (ARI) and dispersion of repolarization (DOR) were analyzed to evaluate the extent of sympathoexcitation and arrhythmogenicity during the left anterior descending coronary artery (LAD) ischemia. Extracellular in-vivo and in-situ spinal dorsal horn (DH) and intermediolateral column (IML) neural recordings were performed using a multichannel microelectrode array inserted at the T2-T3 segment of the spinal cord. SCS was performed for 30 mins at 1 kHz, 0.03 ms, 90% motor threshold. LAD ischemia was induced pre- and 1 min post-SCS to investigate how SCS modulates spinal neural network processing of myocardial ischemia. DH and IML neural interactions, including neuronal synchrony as well as cardiac sympathoexcitation and arrhythmogenicity markers were evaluated during myocardial ischemia pre- vs. post-SCS. ARI shortening in the ischemic region and global DOR augmentation due to LAD ischemia was mitigated by SCS. Neural firing response of ischemia-sensitive neurons during LAD ischemia and reperfusion was blunted by SCS. Further, SCS showed a similar effect in suppressing the firing response of IML and DH neurons during LAD ischemia. SCS exhibited a similar suppressive impact on the mechanical, nociceptive and multimodal ischemia sensitive neurons. The LAD ischemia and reperfusion-induced augmentation in neuronal synchrony between DH-DH and DH-IML pairs of neurons were mitigated by the SCS. These results suggest that SCS is decreasing the sympathoexcitation and arrhythmogenicity by suppressing the interactions between the spinal DH and IML neurons and activity of IML preganglionic sympathetic neurons.